Clinical characteristics and pregnancy outcomes of infertile patients with endometriosis and endometrial polyps: A retrospective cohort study - Shunhe Lin; Xi Xie; Yuyan Guo; Hong Zhang; Chaobin Liu; Jingsong Yi; Yanzhao Su; Qicheng Deng; Weipei Zhu (Elsevier, 2020)
Objective: The aim of this study was to discuss the clinical characteristics and the prognosis of surgically diagnosed endometriosis complicated by endometrial polyps and investigate the association between pregnancy outcomes during subsequent pregnancies. Materials and methods: From January 2013 to December 2016, 1263 infertile patients were enrolled in the study. We identified 451 patients with endometriosis, and divided them into a polyp group (n = 204) and a non-polyp group (n = 247) based on whether or not they were associated with endometrial polyps. Postoperative clinical pregnant women (n = 82) among the polyp group were then classified into a study group and a control group composed of those undergoing a singleton pregnancy (n = 164) who delivered during the same time period. Clinical statuses and complications during pregnancy and delivery were collected from hospitals and by telephone interviews and surveys through the mail. Results: The prevalence rate of endometriosis infertile group was obviously higher than the non-endometriosis infertile group ([45.23%; 204/451] versus [17.12%; 139/812]). Women suffering from stage 1 to 4 endometriosis had a 42.44% (73/172), 40.69% (59/145), 55.89% (38/68) and 51.52% (34/66) occurrence rate of endometrial polyps, respectively. The frequency of endometrial polyps for stage 3 and 4 patients was obviously higher than that of stage 1 and 2 patients ([53.73%; 72/134] versus [41.64%; 132/317]). Moreover, the occurrence rate of deep infiltrating endometriosis (DIE) was 57.81% (37/64), which was obviously higher than that of ovarian endometriosis (42.42%; 98/231) and peritoneal endometriosis (44.23%; 69/156). Of the 204 women diagnosed with posterior endometrial polyps, 89 became pregnant, 7 pregnancies ended in a spontaneous abortion, and 82 successfully delivered a baby. The clinical pregnancy rate of patients in stages 1 and 2 was wholly higher than that of patients in stages 3 and 4 ([48.70%; 56/115] versus [37.71%; 26/82]). The postsurgical pregnancy status of patients suffering from peritoneal endometriosis was slightly better than those with ovarian or DIE, but differences were not statistically significant (P = 0.626). We also found that the pregnancy rate was statistically elevated in patients whose EFI scores range from 7 to 10. When compared to the control group, women with endometriosis and endometrial polyps had a higher risk of their pregnancy being complicated by placenta previa (13.41%) and cesarean delivery (59.76%). Conclusion: Patients with endometriosis have a higher frequency of endometrial polyps. We found that a combined hysteroscopy and laparoscopy surgical procedure is an effective way to increase pregnancy rates. Different endometriosis stages and types in patients were associated with clinical pregnancy and spontaneous abortion rates. Women affected by both endometriosis and endometrial polyps have an independently elevated risk of placenta previa and cesarean delivery during pregnancy.